L'esempio di Silvio Trentin Scritti 1954-1991 - Bobbio, Norberto (Carte, Studi e Opere - Centro Trentin di Venezia, 2020)
Using unpublished documents, this volume restores the meeting between two masters in a historical and ideal way: Norberto Bobbio and Silvio Trentin. Through the writings which Bobbio dedicated to Trentin between 1954 and 1991, the readers are introduced to Trentin's world. They gradually discover Trentin's exemplary biography, his clear moral personality and his commitment to anti-fascism and the Resistance, as well as the great themes of his work as a jurist and political thinker: the criticism of fascism, federalism and the idea of the 'third way'. As Bobbio observes, the fundamental reason why Trentin represents a still valuable example is that, through his life and thought, he has perfectly embodied the conception of politics as a desire of justice, as opposed to the will to dominate.